Tiotropium modulates transient receptor potential V1 (TRPV1) in airway sensory nerves: A beneficial off-target effect? - Birrell,MA; Bonvini,SJ; Dubuis,E; Maher,SA; Wortley,MA; Grace,MS; Raemdonck,K; Adcock,JJ; Belvisi,MG (Journal of Allergy and Clinical Immunology, 2014)
BackgroundRecent studies have suggested that the long-acting muscarinic receptor antagonist tiotropium, a drug widely prescribed for its bronchodilator activity in patients with chronic obstructive pulmonary disease and asthma, improves symptoms and attenuates cough in preclinical and clinical tussive agent challenge studies. The mechanism by which tiotropium modifies tussive responses is not clear, but an inhibition of vagal tone and a consequent reduction in mucus production from submucosal glands and bronchodilation have been proposed.ObjectiveThe aim of this study was to investigate whether tiotropium can directly modulate airway sensory nerve activity and thereby the cough reflex.MethodsWe used a conscious cough model in guinea pigs, isolated vagal sensory nerve and isolated airway neuron tissue– and cell-based assays, and in vivo single-fiber recording electrophysiologic techniques.ResultsInhaled tiotropium blocked cough and single C-fiber firing in the guinea pig to the transient receptor potential (TRP) V1 agonist capsaicin, a clinically relevant tussive stimulant. Tiotropium and ipratropium, a structurally similar muscarinic antagonist, inhibited capsaicin responses in isolated guinea pig vagal tissue, but glycopyrrolate and atropine did not. Tiotropium failed to modulate other TRP channel–mediated responses. Complementary data were generated in airway-specific primary ganglion neurons, demonstrating that tiotropium inhibited capsaicin-induced, but not TRPA1-induced, calcium movement and voltage changes.ConclusionFor the first time, we have shown that tiotropium inhibits neuronal TRPV1-mediated effects through a mechanism unrelated to its anticholinergic activity. We speculate that some of the clinical benefit associated with taking tiotropium (eg, in symptom control) could be explained through this proposed mechanism of action.